Pencil Beam Scanning Proton Therapy for Adolescents and Young Adults with Head and Neck Sarcomas - Miriam Vázquez, MD; Katja Baust, MSc; Amaia Ilundain, MD; Dominic Leiser, MD; Barbara Bachtiary, MD; Alessia Pica, MD; Ulrike L. Kliebsch, PhD; Gabriele Calaminus, MD; Damien C. Weber, MD (International Journal of Particle Therapy, 2023)
Purpose: To assess clinical outcomes of adolescents and young adults (AYAs) with head and neck sarcomas (HNSs) treated with pencil beam scanning proton therapy (PBSPT) and to report quality of life (QoL). Materials and Methods: Twenty-eight AYAs (aged 15 to 39 years) with HNS treated between January 2001 and July 2022 at our institution were included. The median age was 21.6 years. Rhabdomyosarcoma (39.3%), Ewing sarcoma (17.9%), chondrosarcoma (14.3%), and osteosarcoma (14.3%) were the most frequent diagnoses. Three (10.7%) patients were metastatic before PBSPT and 13 (46.4%) patients had a tumor with intracranial extension. The median total radiation dose was 63 GyRBE (range, 45 to 74 GyRBE). Thirteen (46.4%) patients received concomitant chemotherapy. Toxicity was reported according to the Common Terminology Criteria for Adverse Events (CTCAE), version 5.0 (US National Institutes of Health, Bethesda, Maryland). Survival was estimated using the Kaplan-Meier method. QoL was assessed using a PEDQOL (Pediatric Quality of Life Questionnaire) questionnaire. Self-reported outcomes were assessed using institutional questionnaires. Results: With a median follow-up of 57 months (range, 3.7 to 243 months), 5 patients (17.8%) had local failure (LF) only, 2 (7.1%) experienced distant failure (DF) only, and 2 (7.1%) had LF and DF. The estimated 5-year local control (LC) and distant control (DC) rates were 71.8% and 80.5%, respectively. The median times to LF and DF were 13.4 and 22.2 months, respectively. Four (14.3%) patients died, all but one from their HNS. Estimated 5-year overall survival was 90.7%. Six (21.4%) patients developed nonocular grade ≥3 toxicity, which consisted of otitis media (n = 2), hearing impairment (n = 2), osteoradionecrosis (n = 1), and sinusitis (n = 1). Four (14.3%) patients developed cataracts that required surgery. The 5-year freedom from nonocular grade 3 toxicity was 91.1%. No grade 4 or higher toxicity was observed. Adolescents rated their quality of life before treatment worse than their parents did. Conclusion: Excellent outcomes with acceptable late-toxicity rates were observed for AYAs with HNS after PBSPT.